Guillain-Barré Syndrome Associated with COVID-19: A Neurochallenge!! - T S Ravindra; Dilmo Yeldo; B S Arjun (Wolters Kluwer Medknow Publications, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent for Coronavirus disease 2019 (COVID-19), originated in Wuhan, China in the fall of 2019 which has soon become a global pandemic engulfing the entire world, presents with a myriad of symptoms from asymptomatic to severe disease with acute respiratory distress syndrome and multiple organ dysfunction and severe inflammatory response. New associations and clinical problems keep appearing with the new virus and here, we are reporting a case of Guillain-Barré syndrome (GBS) presented to us with complaints of progressive proximal muscle weakness and bilateral facial paralysis. The initial nerve conduction study was normal, but clinical examination showed us a picture of acute inflammatory demyelinating polyradiculoneuropathy and the patient was treated with intravenous immunoglobulin to which the patient responded dramatically. Repeat nerve conduction study showed typical features of GBS. Thus, a differential diagnosis of GBS should be kept in mind by all physicians/neurologists who encounter any neurological symptoms (especially muscle weakness) while treating or post-COVID-19 infection.